2015
DOI: 10.2172/1224985
|View full text |Cite
|
Sign up to set email alerts
|

SIGMA Release v1.2 - Capabilities, Enhancements and Fixes

Abstract: 60439. For information about Argonne and its pioneering science and technology programs, see www.anl.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This process flow also prohibits the component solvers from performing any runtime spatial adaptivity, since the remapping weights have to be recomputed dynamically after any changes in grid positions. To overcome such deficiencies, and to accelerate the current coupling workflow, recent efforts have been undertaken to implement a fully integrated remapping weight generation process within E3SM using a scalable infrastructure provided by the topology, decomposition, and data-aware Mesh Oriented datABase (MOAB; http://sigma.mcs.anl.gov/ moab-library, last access: 16 May 2020) (Tautges et al, 2004;Mahadevan et al, 2015) and TempestRemap (Ullrich et al, 2013) software libraries as shown in Fig. 1b.…”
Section: Hub-and-spoke Vs Distributed Coupling Workflowmentioning
confidence: 99%
See 2 more Smart Citations
“…This process flow also prohibits the component solvers from performing any runtime spatial adaptivity, since the remapping weights have to be recomputed dynamically after any changes in grid positions. To overcome such deficiencies, and to accelerate the current coupling workflow, recent efforts have been undertaken to implement a fully integrated remapping weight generation process within E3SM using a scalable infrastructure provided by the topology, decomposition, and data-aware Mesh Oriented datABase (MOAB; http://sigma.mcs.anl.gov/ moab-library, last access: 16 May 2020) (Tautges et al, 2004;Mahadevan et al, 2015) and TempestRemap (Ullrich et al, 2013) software libraries as shown in Fig. 1b.…”
Section: Hub-and-spoke Vs Distributed Coupling Workflowmentioning
confidence: 99%
“…Since both libraries are written in C++, direct inheritance of key data structures such as the GridElements (mesh) and OfflineMap (projection weights) are available to minimize data movement between the libraries. Additionally, Fortran codes such as E3SM can invoke computations of the intersection mesh and the remapping weights through specialized language-agnostic interfaces in MOAB: iMOAB (Mahadevan et al, 2015). These interfaces offer the flexibility to query, manipulate, and transfer the mesh between groups of processes that represent the component and coupler processing elements.…”
Section: Note On Mbtr Remapper Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…This process flow also prohibits the component solvers from performing any runtime spatial adaptivity, since the remapping weights have to be re-computed dynamically after any changes in grid positions. To overcome such deficiencies, and to accelerate the current coupling workflow, recent efforts have been undertaken to implement a fully integrated remapping weight generation process within E3SM using a scalable infrastructure provided by the topology, decomposition and data-aware Mesh Oriented datABase (MOAB) Tautges et al (2004); Mahadevan et al (2015) and TempestRemap Ullrich et al (2013) software libraries as shown in Fig. 1 (right).…”
mentioning
confidence: 99%
“…combination of implementations in MOAB and TempestRemap libraries. Since both the libraries are written in C++, direct inheritance of key datastructures such as the GridElements (mesh) and OfflineMap (projection weights) are available to minimize data movement between the libraries.Additionally, Fortran codes such as E3SM can invoke computations of the intersection mesh and the remapping weights through specialized language-agnostic interfaces in MOAB: iMOABMahadevan et al (2015). These interfaces offer the flexibility to query, manipulate and transfer the mesh between groups of processes that represent the component and coupler processing elements.Using the iMOAB interfaces, the E3SM coupler can coordinate the online remapping workflow during the setup phase of the simulation, and compute the projection operators for component and scalar or vector coupled field combinations.…”
mentioning
confidence: 99%